Polymerization Of Glyserol Monostearat With Azelaic Acid - Adriani, Nina; Zakaria, Zuriati (Program Studi Pendidikan Kimia, Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2014)
In this study, polymerization reaction between glycerol monostearat (1g, 0.002mol) with azelaic acid (2g, 0.005mol) carried out. Production process of this polymer is made in temperature 60-80â°C and pressure ( 150Pa) by using Novozyms enzyme catalyst 435 for 3 hours. Starting material is glycerol monostearat (MAG) produced through esterification reaction in temperature 60-80â°C for 4 hours by using enzyme catalyst are Rhizomucor miehei and Lipozim TL IM. After that  purification of MAG carried out through winterization process by using centrifugal that separate MAG and hexane solution. It kept at 0â°C for 24 hours until precipitation formed through centrifugation (3,500 rpm, 20 means, 4â°C). After MAG produced, it will analyzed by HPLC and found as much as content 100% of both MAG. Further analysis are 1H and 13C NMR and FTIR to know absorption spectrum and peak produced from MAG and polymer.